Untangling factors influencing social networking sites use among older adults: a literature review - Chew, Tze Ha; Chin, Pei Yee; Leau, Yu-Beng (Springer Verlag, 2022)
While social networking sites (SNSs) have become a popular communication tool for younger generations, their use has gained popularity among older adults in recent years. However, studies related to SNSs use and older adults are still in scarcity and lacking a rigorous understanding of what influences them to use SNSs. This literature review aims to provide an overview of existing literature on SNSs and older adults. This review identified 28 relevant articles published between 2010 and 2020 and provided an overview of the older adults’ SNSs usage behaviors, antecedents, and associated outcomes. Older people use mainly SNSs to connect to friends, followed by family, new friends, children, and others. The review has shown that the SNSs use among older adults is generally influenced by ten tentative factors that can be categorized into three dimensions: technological (e.g. perceived usefulness, perceived ease of use, perceived enjoyment, quality of content); individual (e.g. trust, self-efficacy, knowledge sharing, compatibility); and social (e.g. social influence, social connectedness). This paper contributes to the Information Systems (IS) field by consolidating previous knowledge about the influencing factors and outcomes SNSs use among elderly people and discussing future research.